Multidimensional Sustainability Evaluation of Community-Based Material Recovery Facilities (TPS3R) and Strategies for Strengthening Regional Waste Management Systems: A Case Study in Mojokerto Regency - SYUKRON, MOCHAMAD (Journal of Environmental Engineering and Sustainable Technology, 2025)
Mojokerto Regency faces a significant waste crisis, with the Tempat Pengolahan Sampah Reduce-Reuse-Recycle (TPS3R) program contributing a negligible 0.015% to regional waste reduction. This failure suggests deep-seated systemic barriers beyond physical infrastructure. This study aims to analyze the sustainability status of the TPS3R program and formulate an integrated optimization strategy to achieve financial autonomy and institutional support. A quantitative assessment using Multidimensional Scaling (MDS) via RAPFISH was employed on a "positive deviance" case study, TPS3R Trawas Berseri Berdikari. The results reveal a critical paradox: while Legal & Institutional (89.43) and Technical (85.51) dimensions are "Highly Sustainable," the facility suffers from fundamental "financial fragility" (Economic score 73.24) and "disconnected governance." Despite its status as a best-practice model, the facility relies on a Rp 5,000,000 monthly subsidy to cover operational deficits. To address this, the research formulates an Integrated Optimization Strategy that pivots from a project-based to a service-based model. Key strategies include (1) Economic Diversification through premium compost marketing to tourism sectors to secure financial independence, (2) Institutional Reform transforming the local government from a passive regulator to an active technical facilitator, and (3) Asset Revitalization to optimize stagnant technology. These findings provide a replicable roadmap for policymakers to revitalize failing infrastructure into autonomous social enterprises, contributing directly to SDG 11.